LEGAL PROTECTION FOR BUYERS FOR SELLING OF LAND RELATED TO BUDEL PAILIT OBJECT - Nuhriwin; M. Sudirman (Research Parks Publishing LLC, 2021)
The research method used in this research is the normative juridical method, carried out as an effort to obtain the necessary data regarding the problem. The data used are secondary data consisting of primary, secondary and tertiary legal materials. The data was collected by means of library research by studying the literature related to the sale and purchase of land, contract law, laws and regulations regarding bankruptcy and legal protection for buyers